Providing Education for People with Diabetes in The Era of Covid-19 - Fitri Fujiana; Sukarni Sukarni; Triyana Harlia Putri; Titan Ligita (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Indonesia has been grieving since the emergence of COVID-19 which is the biggest outbreak of all time. Confirmed cases of COVID-19 in Indonesia reached 1.2 million people, cases died 32,936 people, and around 510 districts and cities were affected, including in West Kalimantan. Patients with diabetes mellitus as one of the comorbid groups who feel the impact of the implementation of activity restrictions. The high incidence of COVID 19 and the enactment of activity restrictions make it difficult for diabetics and worry to access health facilities. This causes diabetics to have limited access to accurate health information related to health care and diabetes wounds suffered. This is experienced by diabetics who usually check their health at one of diabetes and diabetes wound care clinics in Pontianak City. The community service team, majoring in nursing, Faculty of Medicine, Tanjungpura University, provided a solution regarding this phenomenon, by facilitating the provision of health education for diabetics. Health education is provided through three stages, namely, preparation, implementation and evaluation. Preparation begins with screening potential participants. The education was provided virtually in four sessions of material and question and answer. For evaluation, pre and posttest were carried out. The result of this virtual health education was an increase in participants' knowledge regarding diabetes care and diabetic foot wounds after being given the material. In addition to the materials, participants also received pocketbooks and educational videos that could be read and used as care guides while at home.